Preparation method and application of coating enhanced nano silver powder

Through polyaniline coating and partially reduced graphene oxide composite technology, the shortcomings of nano-silver coatings in antibacterial effects, antistatic properties and wear resistance are solved, and better application effects in medical environments are achieved.

CN119910193AActive Publication Date: 2025-05-02SUZHOU YINRUN PHOTOELECTRIC TECH CO LTD

Patent Information

Application Number
CN202510412831.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-05-02
Estimated Expiration
2045-04-03

AI Technical Summary

Technical Problem

Existing nanosilver coatings have shortcomings in the stability and durability of antibacterial effects, and cannot fully meet the strict requirements for antistatic and wear resistance in medical environments.

Method used

Through the technology of polyaniline coating and partially reducing graphene oxide composite, the dispersion and stability of nanosilver particles are improved, their antibacterial properties are enhanced, and the conductive and mechanical properties of the coating are improved through the introduction of graphene.

Benefits of technology

The long-lasting antibacterial effect of nano-silver coatings is achieved, and the antistatic properties and wear resistance are enhanced, making the coatings have better long-term application in medical environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119910193A_ABST
    Figure CN119910193A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of coating enhanced nano silver powder. The preparation method comprises the following steps: S1, preparing nano silver by taking silver nitrate as a silver source and polyethyleneimine as a reducing agent; s2, carrying out coating modification on the nano-silver by adopting aniline and ammonium persulfate under an acidic condition; s3, modifying the polyaniline coated nano-silver by adopting chloroacetic acid to obtain chloroacetic acid modified polyaniline coated nano-silver; s4, preparing a modified graphene oxide dispersion liquid; s5, partially reducing the graphene oxide; s6, partially reduced graphene oxide is adopted to load the chloroacetic acid modified polyaniline coated nano-silver, polyaniline coating and reduced graphene oxide compounding are carried out, and the dispersity and stability of nano-silver particles are effectively improved. The oxidation state of polyaniline promotes the release of silver ions through an electron transfer effect, so that the antibacterial effect is enhanced; and the partially reduced graphene oxide synergistically accelerates the release of silver ions, so that the antibacterial property is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano silver antibacterial coatings, and in particular to a preparation method and application of coated enhanced nano silver powder. Background Art

[0002] Nanosilver (AgNPs) is widely used in the fields of medical treatment, hygiene, food packaging, etc. due to its excellent antibacterial properties. Nanosilver particles have a large specific surface area and surface effect, and can release silver ions to interact with bacterial cell walls, thereby inhibiting the growth and reproduction of bacteria. The antibacterial mechanism of silver ions is mainly to destroy the structure of bacterial cell walls, interfere with their metabolic processes and DNA replication, and ultimately lead to bacterial death. Therefore, nanosilver coatings play an important role in preventing the spread of bacteria in places such as hospitals and clinics.

[0003] Hospitals, operating rooms, emergency rooms and other medical environments have very high requirements for coatings. In addition to having antibacterial functions to prevent hospital infections, coatings also need to meet other performance requirements. Especially on the surface of medical equipment, such as diagnostic equipment, monitoring instruments, infusion pumps, etc., these devices are not only often exposed to high-frequency cleaning and disinfection environments, but are also susceptible to static electricity accumulation. Static electricity may interfere with the normal operation of precision equipment and even cause equipment failure. Therefore, the coating also needs to have antistatic properties to ensure the stability and safety of the equipment.

[0004] In addition, the surface of medical equipment often needs to withstand frequent wiping, disinfection and long-term use, so the coating must also have good wear resistance to avoid loss of function due to friction during cleaning and use.

[0005] Although nanosilver coatings have excellent antibacterial performance, they still face certain technical difficulties in practical applications. First, nanosilver particles are prone to agglomeration, resulting in uneven distribution of silver particles in the coating, which in turn affects the stability and durability of its antibacterial effect. In addition, the uneven release of silver ions may cause the antibacterial performance to decline over time. Secondly, existing nanosilver coatings often cannot fully meet the strict requirements of the medical environment in terms of antistatic and wear resistance. For example, static electricity accumulation may cause electrical interference to precision medical equipment, and insufficient wear resistance of the coating will cause damage to the surface coating of the equipment, thereby affecting the normal function and service life of the equipment.

[0006] Therefore, developing a nanosilver coating that can ensure long-lasting antibacterial effect while also having excellent antistatic and wear resistance has become a technical problem that needs to be solved urgently in the medical environment. Summary of the invention

[0007] In view of the above analysis, the present invention aims to provide a preparation method and application of coated enhanced nano silver powder to solve the problems in the background technology.

[0008] The purpose of the present invention is mainly achieved through the following technical solutions:

[0009] A method for preparing coated enhanced nano silver powder comprises the following steps:

[0010] S1: Silver nitrate was used as the silver source and polyethyleneimine was used as the reducing agent to prepare nanosilver;

[0011] S2: using aniline and ammonium persulfate to coat and modify the nano-silver under acidic conditions to obtain polyaniline-coated nano-silver;

[0012] S3: using chloroacetic acid to modify the polyaniline-coated nanosilver to obtain chloroacetic acid-modified polyaniline-coated nanosilver;

[0013] S4: oxidizing graphite to prepare graphene oxide, and then modifying it with polyethyleneimine to obtain a modified graphene oxide dispersion;

[0014] S5: partially reducing the graphene oxide using sodium hydride to obtain a reduced graphene aqueous dispersion;

[0015] S6: using reduced graphene oxide to load the chloroacetic acid modified polyaniline to coat the nano-silver, to obtain the coated enhanced nano-silver powder.

[0016] In one or more embodiments, the specific process of step S1 is:

[0017] According to the weight components, 5-8 parts of silver nitrate are uniformly dispersed in 100 parts of deionized water to obtain a first reaction liquid; 25-40 parts of polyethyleneimine are uniformly dispersed in 250 parts of deionized water to obtain a second reaction liquid; the first reaction liquid and the second reaction liquid are mixed, the pH value is adjusted to 1-2, and the mixture is stirred uniformly and fully reacted in an oil bath at 80-100° C. to obtain a third reaction liquid; the third reaction liquid is filtered, washed and dried to obtain nano silver.

[0018] In one or more embodiments, the specific process of step S2 is: take 1 part of the nanosilver and 0.1-0.2 parts of sodium dodecyl sulfate, ultrasonically disperse them in deionized water, then add 1.7-3.4 parts of aniline and 4-6 parts of ammonium persulfate, adjust the pH value to 1-2, stir the reaction at 0-5°C for 1-2h, then perform solid-liquid separation, wash the obtained solid with ethanol and then dry it to obtain polyaniline-coated nanosilver.

[0019] In one or more embodiments, the specific process of step S3 is:

[0020] Take 1 part of polyaniline-coated nanosilver, add 0.5-1.5 parts of chloroacetic acid and dissolve in deionized water, adjust the pH value of the solution to 1-2, and stir the reaction for 3-5 hours;

[0021] After the reaction is completed, the mixture is filtered, washed, and cleaned with ethanol, and finally dried at 60-80° C. to obtain chloroacetic acid-modified polyaniline-coated nanosilver.

[0022] In one or more embodiments, the specific process of step S4 is: 1-2 parts of graphite are uniformly dispersed in 50 parts of concentrated sulfuric acid, and 4-10 parts of concentrated nitric acid are added, stirred in an ice water bath, and slowly heated to room temperature, and the stirring reaction is continued for 6-12 hours to generate graphene oxide; after the reaction is completed, multiple centrifugal washings are performed to remove residual acidic substances and unreacted impurities, and dispersed in 200 parts of deionized water to obtain a graphene oxide aqueous dispersion; then ultrasonic treatment is performed at a frequency of 40-80 kHz, a power of 200-300W, and an ultrasonic time of 30-40min to ensure that the graphene oxide is completely dispersed; then, 2-8 parts of polyethyleneimine are added to the graphene oxide dispersion, and the stirring reaction is continued for 2-3h to obtain a modified graphene oxide dispersion.

[0023] In one or more embodiments, the specific process of step S5 is: adding 1-2 parts of reducing agent sodium hydride to the modified graphene oxide dispersion, stirring and reacting for 2-3 hours to obtain a reduced graphene aqueous dispersion.

[0024] In one or more embodiments, the specific process of step S6 is: take 1 part of the chloroacetic acid modified polyaniline coated nanosilver, add 0.1-0.2 parts of sodium dodecyl sulfate, and ultrasonically disperse it in 100 parts of deionized water, and the ultrasonic frequency is 40-60 kHz and the power is 200-400 W to ensure that the nanosilver particles are evenly dispersed; then mix it with the reduced graphene aqueous dispersion; obtain a composite reaction solution; adjust the pH value of the solution to 1-1.5, stir the reaction at 0-5°C for 1-2h, separate the solid and liquid of the reactant, and then wash and dry it to obtain the reduced graphene-loaded nanosilver, that is, the coated enhanced nanosilver powder.

[0025] In a second aspect, the present invention provides an application of coated enhanced nano silver powder in coatings.

[0026] The present invention provides a nano silver coating in a third aspect, comprising: 10-15 parts of coated enhanced nano silver powder, 30-40 parts of epoxy resin, 5-10 parts of curing agent diaminocyclohexane, 1-2 parts of dispersant sodium dodecyl sulfate, 0.5-2 parts of plasticizer dibutyl phthalate and 5-10 parts of ethanol.

[0027] The present invention provides a method for nano silver coating in a fourth aspect, comprising the following steps:

[0028] Take 10-15 parts of coated enhanced nano silver powder, add it to 60 parts of deionized water, and disperse it evenly by ultrasonication;

[0029] Take 30-40 parts of epoxy resin and place them in a high shear mixer for later use;

[0030] Gradually add the coated enhanced nanosilver liquid into the epoxy resin while stirring;

[0031] Add 5-10 parts of curing agent diaminocyclohexane and 0.5-2 parts of plasticizer dibutyl phthalate to the high shear mixer and continue to stir evenly to ensure that the curing agent is completely distributed in the epoxy resin;

[0032] Finally, add 5-10 parts of ethanol to adjust the viscosity of the coating;

[0033] The coating is poured into a mold, placed in an oven, and cured at 60-80° C. for 2-4 hours to obtain the nano silver coating.

[0034] The principles and mechanisms of the present invention are as follows:

[0035] The antibacterial properties of silver nanoparticles mainly depend on the silver ions (Ag + ) release. Silver ions can destroy bacterial cell walls, inhibit DNA synthesis and interfere with bacterial metabolic processes, and therefore have a broad-spectrum antibacterial effect. However, nanosilver particles are prone to agglomeration, resulting in a reduction in their surface area and a weakening of their antibacterial effect. In order to solve this problem, the present invention effectively improves the dispersibility and stability of nanosilver by coating nanosilver with polyaniline and compounding partially reduced graphene oxide, and enhances its antibacterial performance.

[0036] As a conductive polymer material, polyaniline (PANI) can effectively prevent the aggregation and precipitation of silver particles while coating nanosilver particles. Polyaniline can not only uniformly coat nanosilver and protect silver particles from oxidation, but also enhance the long-term stability of silver particles.

[0037] The formation of the oxidized state of polyaniline promotes the release of silver ions. In step S2, ammonium persulfate (APS) reacts with aniline as an oxidant and initiator to oxidize the aniline monomer to form oxidized polyaniline (PANI-EB, emeraldine base). In this process, ammonium persulfate converts polyaniline into an oxidized state through an oxidation reaction. This process gives polyaniline the semiconductor properties of π-electrons. The oxidized state of polyaniline has a strong electron-accepting ability, which can change the electronic environment on the surface of silver nanoparticles. When polyaniline is in an oxidized state, polyaniline promotes an oxidation reaction on the surface of silver nanoparticles through electron transfer, and silver is converted from a metallic state to silver ions (Ag +). This oxidation process accelerates the release of silver ions and enhances the antibacterial effect.

[0038] Specifically, the oxidation state of polyaniline provides a pathway for electron transfer, allowing silver ions to be released more rapidly from the surface of silver particles into the solution, thereby enhancing the antibacterial effect of the composite material and the bioactivity of silver.

[0039] The introduction of partially reduced graphene oxide and the synergistic effect of silver ion release play an important role in the introduction of partially reduced graphene oxide (rGO) in the composite material. Graphene oxide itself has abundant oxygen functional groups, which interact strongly with the surface of polyaniline and silver particles, effectively avoiding the agglomeration and precipitation of silver particles. Partially reduced graphene has good conductivity and can form a continuous conductive network in the composite material, which is conducive to eliminating static electricity.

[0040] The conductive network of graphene provides an electron transfer channel for polyaniline, promoting the rapid release of silver ions. Since graphene can quickly migrate electrons, it further accelerates the formation of the oxidized state of polyaniline, thereby accelerating the release of silver ions. The presence of graphene not only improves the conductivity of the composite material, but also makes the release of silver ions more uniform and lasting, further enhancing the antibacterial effect. The interaction with the oxygen functional groups on the surface of graphene oxide not only improves the dispersion and stability of graphene oxide, but also enhances the conductivity of graphene oxide through charge transfer. Graphene oxide itself has strong electronic conductivity, and the introduction of polyethyleneimine can optimize the electron transmission path, providing the composite material with better conductivity and antibacterial effect.

[0041] As a two-dimensional carbon material, graphene has excellent mechanical properties, especially plays an important role in enhancing the tensile strength, hardness and toughness of composite materials. In the present invention, the partially reduced graphene not only improves the conductivity of the composite material, but also significantly enhances the mechanical properties of the coating. The introduction of graphene forms a strong network structure, which can effectively improve the scratch resistance, wear resistance and compression resistance of the coating, thereby enhancing the mechanical strength and durability of the coating in actual use.

[0042] Chloroacetic acid can react with the amino groups in polyaniline to introduce carboxylic acid groups (-COOH). This modification increases the polarity of polyaniline, making it more compatible with the epoxy resin matrix. In addition, the carboxylic acid groups introduced on the surface of polyaniline can undergo a ring-opening reaction with the epoxy groups during the epoxy resin curing process to form an ether structure, thereby improving the interfacial bonding strength and adhesion, and enhancing the mechanical properties and chemical stability of the coating.

[0043] The combination of nanosilver, polyaniline and graphene not only improves the antibacterial effect, but also enhances the conductivity, mechanical properties, stability and durability of the composite material, making the composite material have better long-term applicability under different environmental conditions.

[0044] Compared with the prior art, the present invention has at least the following beneficial effects:

[0045] (1) The present invention effectively improves the dispersibility and stability of nanosilver particles through the technology of polyaniline coating and partially reduced graphene oxide composite. The oxidation state of polyaniline promotes the release of silver ions through electron transfer, thereby enhancing the antibacterial effect; while the conductivity of partially reduced graphene oxide provides an electron transfer channel, accelerates the release of silver ions, and further improves the antibacterial performance. The introduction of graphene not only enhances the conductivity of the coating, effectively reduces the surface resistance of the coating, but also significantly improves the mechanical properties and durability of the coating. The modification of chloroacetic acid improves the compatibility of polyaniline and epoxy resin, further enhancing the overall performance of the composite coating. The synergistic effect of the three makes the composite material show significant advantages in antibacterial properties, conductivity, mechanical properties, durability and environmental adaptability, and is suitable for applications in a variety of harsh environments.

[0046] (2) The present invention can achieve stable coating and dispersion of nanosilver at lower temperatures and mild chemical conditions. This makes the production process simpler and more environmentally friendly compared to traditional nanosilver synthesis technology (such as high temperature and high pressure reaction, use of strong reducing agents, etc.).

[0047] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0049] Figure 1 The present invention is a process flow chart for preparing the coated enhanced nano silver powder. DETAILED DESCRIPTION

[0050] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the present invention should not be limited to these embodiments. Unless otherwise stated, they can be replaced by other alternative features that are equivalent or have similar purposes. Unless otherwise stated, each feature is just an example of a series of equivalent or similar features. The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. In the following examples, unless otherwise specified, concentration % refers to mass percentage; the substances used can all be obtained commercially.

[0051] The reagents used in the embodiments and comparative examples of the present invention are as follows, and those skilled in the art may make replacements according to actual needs, which are not intended to limit the present invention.

[0052] The epoxy resin used was epoxy resin E51 purchased from Shandong Deyuan Epoxy Technology Co., Ltd.

[0053] Aniline was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0054] Silver nitrate was purchased from Tianjin North Tianyi Chemical Reagent Factory.

[0055] Polyethyleneimine was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with an average MW of 250,000.

[0056] Ammonium persulfate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., electrophoresis grade, ≥98%.

[0057] Figure 1 The preparation process of the coated enhanced nano silver powder of the present invention is shown.

[0058] Example 1

[0059] According to the weight components, 6 parts of silver nitrate are uniformly dispersed in 100 parts of deionized water to obtain a first reaction liquid; 30 parts of polyethyleneimine are uniformly dispersed in 250 parts of deionized water to obtain a second reaction liquid; the first reaction liquid and the second reaction liquid are mixed, the pH value is adjusted to 1.5, and the mixture is stirred evenly and fully reacted in an oil bath at 90° C. to obtain a third reaction liquid; the third reaction liquid is filtered, washed and dried to obtain nano silver.

[0060] Take 1 part of the nanosilver and 0.1 part of sodium dodecyl sulfate, ultrasonically disperse them in deionized water, then add 1.7 parts of aniline and 4 parts of ammonium persulfate, adjust the pH value to 1, stir and react at 0°C for 1 hour, then perform solid-liquid separation, wash the obtained solid twice with ethanol and then vacuum dry to obtain polyaniline-coated nanosilver.

[0061] Take 1 part of polyaniline-coated nanosilver, add 0.5 parts of chloroacetic acid and dissolve in deionized water, adjust the pH value of the solution to 1, stir and react for 3 hours,

[0062] After the reaction was completed, the mixture was filtered, washed, and cleaned with ethanol three times, and finally dried at 60° C. to obtain chloroacetic acid-modified polyaniline-coated nanosilver.

[0063] One part of graphite is uniformly dispersed in 50 parts of concentrated sulfuric acid, and 4 parts of concentrated nitric acid are added, stirred in an ice-water bath, and slowly heated to room temperature, and the stirring reaction is continued for 6 hours to generate graphene oxide; after the reaction is completed, it is centrifuged and washed several times to remove residual acidic substances and unreacted impurities, and then dispersed in 200 parts of deionized water to obtain a graphene oxide aqueous dispersion; then ultrasonic treatment is performed at a frequency of 40 kHz, a power of 200 W, and an ultrasonic time of 30 minutes to ensure that the graphene oxide is completely dispersed; then, 2 parts of polyethyleneimine are added to the graphene oxide dispersion, and the stirring reaction is continued for 2 hours to obtain a modified graphene oxide dispersion.

[0064] One portion of reducing agent sodium hydride was added to the modified graphene oxide dispersion, and the mixture was stirred for reaction for 2 hours. After the reaction was completed, a reduced graphene aqueous dispersion was obtained.

[0065] Take 1 part of the chloroacetic acid modified polyaniline coated nanosilver, add 0.1 part of sodium dodecyl sulfate, and ultrasonically disperse it in 100 parts of deionized water. The ultrasonic treatment frequency is 40 kHz and the power is 200 W to ensure that the nanosilver particles are evenly dispersed; then mix it with the reduced graphene aqueous dispersion; obtain a composite reaction solution; adjust the solution pH value to 1, stir and react at 0°C for 1 hour, separate the reactant into solid and liquid, and then wash and dry it to obtain reduced graphene-loaded nanosilver, that is, the coated enhanced nanosilver powder.

[0066] Take 10 parts of coated enhanced nano silver powder, add it to 60 parts of deionized water, and disperse it evenly by ultrasonication;

[0067] Take 30 parts of epoxy resin and place them in a high shear mixer for later use;

[0068] Gradually add the coated enhanced nanosilver liquid and 1 part of dispersant sodium dodecyl sulfate into the epoxy resin, stirring while adding;

[0069] Add 5 parts of curing agent diaminocyclohexane and 0.5 parts of plasticizer dibutyl phthalate to the high shear mixer and continue to stir evenly to ensure that the curing agent is completely distributed in the epoxy resin;

[0070] Finally, add 5 parts of ethanol to adjust the viscosity of the coating.

[0071] The coating was poured into a mold, placed in an oven, and cured at 75° C. for 2 hours to obtain the nano silver coating.

[0072] Example 2

[0073] According to the weight components, 8 parts of silver nitrate are uniformly dispersed in 100 parts of deionized water to obtain a first reaction liquid; 40 parts of polyethyleneimine are uniformly dispersed in 250 parts of deionized water to obtain a second reaction liquid; the first reaction liquid and the second reaction liquid are mixed, the pH value is adjusted to 1, and the mixture is stirred evenly and fully reacted in an oil bath at 80° C. to obtain a third reaction liquid; the third reaction liquid is filtered, washed and dried to obtain nano silver.

[0074] Take 1 part of the nanosilver and 0.1 part of sodium dodecyl sulfate, ultrasonically disperse them in deionized water, then add 2 parts of aniline and 6 parts of ammonium persulfate, adjust the pH value to 1, stir and react at 0°C for 1 hour, then perform solid-liquid separation, wash the obtained solid twice with ethanol and then vacuum dry to obtain polyaniline-coated nanosilver.

[0075] Take 1 part of polyaniline-coated nanosilver, add 0.5 parts of chloroacetic acid and dissolve in deionized water, adjust the pH value of the solution to 1, stir and react for 3 hours,

[0076] After the reaction was completed, the mixture was filtered, washed, and cleaned with ethanol three times, and finally dried at 60° C. to obtain chloroacetic acid-modified polyaniline-coated nanosilver.

[0077] One part of graphite is uniformly dispersed in 50 parts of concentrated sulfuric acid, and 4 parts of concentrated nitric acid are added, stirred in an ice-water bath, and slowly heated to room temperature, and the stirring reaction is continued for 8 hours to generate graphene oxide; after the reaction is completed, it is centrifuged and washed several times to remove residual acidic substances and unreacted impurities, and then dispersed in 200 parts of deionized water to obtain a graphene oxide aqueous dispersion; then ultrasonic treatment is performed with a frequency of 80 kHz, a power of 300 W, and an ultrasonic time of 40 minutes to ensure that the graphene oxide is completely dispersed; then, 8 parts of polyethyleneimine are added to the graphene oxide dispersion, and the stirring reaction is continued for 3 hours to obtain a modified graphene oxide dispersion.

[0078] Add 2 parts of reducing agent sodium hydride to the modified graphene oxide dispersion, stir and react for 3 hours, and after the reaction is completed, obtain a reduced graphene aqueous dispersion.

[0079] Take 1 part of the chloroacetic acid modified polyaniline coated nanosilver, add 0.2 parts of sodium dodecyl sulfate, and ultrasonically disperse it in 100 parts of deionized water, and ensure that the nanosilver particles are evenly dispersed by ultrasonic treatment at a frequency of 60 kHz and a power of 400 W; then mix it with the reduced graphene aqueous dispersion; obtain a composite reaction solution; adjust the solution pH value to 1.5, stir and react at 2°C for 2h, separate the reactant into solid and liquid, and then wash and dry it to obtain reduced graphene-loaded nanosilver, that is, the coated enhanced nanosilver powder.

[0080] Take 15 parts of coated enhanced nano silver powder, add it to 60 parts of deionized water, and disperse it evenly by ultrasonication;

[0081] Take 30 parts of epoxy resin and place them in a high shear mixer for later use;

[0082] Gradually add the coated enhanced nanosilver liquid and 1 part of dispersant sodium dodecyl sulfate into the epoxy resin, stirring while adding;

[0083] Add 8 parts of curing agent diaminocyclohexane and 1 part of plasticizer dibutyl phthalate to the high shear mixer and continue to stir evenly to ensure that the curing agent is completely distributed in the epoxy resin;

[0084] Finally, 8 parts of ethanol were added to adjust the viscosity of the coating.

[0085] The coating was poured into a mold, placed in an oven, and cured at 80° C. for 4 hours to obtain the nano silver coating.

[0086] Example 3

[0087] According to the weight components, 6 parts of silver nitrate are uniformly dispersed in 100 parts of deionized water to obtain a first reaction liquid; 30 parts of polyethyleneimine are uniformly dispersed in 250 parts of deionized water to obtain a second reaction liquid; the first reaction liquid and the second reaction liquid are mixed, the pH value is adjusted to 1, and the mixture is stirred evenly and fully reacted in an oil bath at 80° C. to obtain a third reaction liquid; the third reaction liquid is filtered, washed and dried to obtain nano silver.

[0088] Take 1 part of the nanosilver and 0.1 part of sodium dodecyl sulfate, ultrasonically disperse them in deionized water, then add 3 parts of aniline and 5 parts of ammonium persulfate, adjust the pH value to 1, stir and react at 0°C for 1 hour, then perform solid-liquid separation, wash the obtained solid twice with ethanol and then vacuum dry to obtain polyaniline-coated nanosilver.

[0089] Take 1 part of polyaniline-coated nanosilver, add 0.5 parts of chloroacetic acid and dissolve in deionized water, adjust the pH value of the solution to 1, stir and react for 3 hours,

[0090] After the reaction was completed, the mixture was filtered, washed, and cleaned with ethanol three times, and finally dried at 60° C. to obtain chloroacetic acid-modified polyaniline-coated nanosilver.

[0091] One part of graphite is uniformly dispersed in 50 parts of concentrated sulfuric acid, and 4 parts of concentrated nitric acid are added, stirred in an ice-water bath, and slowly heated to room temperature, and the stirring reaction is continued for 10 hours to generate graphene oxide; after the reaction is completed, it is centrifuged and washed several times to remove residual acidic substances and unreacted impurities, and then dispersed in 200 parts of deionized water to obtain a graphene oxide aqueous dispersion; then ultrasonic treatment is performed with a frequency of 70 kHz, a power of 250 W, and an ultrasonic time of 35 minutes to ensure that the graphene oxide is completely dispersed; then, 5 parts of polyethyleneimine are added to the graphene oxide dispersion, and the stirring reaction is continued for 2.5 hours to obtain a modified graphene oxide dispersion.

[0092] One portion of reducing agent sodium hydride was added to the modified graphene oxide dispersion, and the mixture was stirred for reaction for 2 hours. After the reaction was completed, a reduced graphene aqueous dispersion was obtained.

[0093] Take 1 part of the chloroacetic acid modified polyaniline coated nanosilver, add 0.1 part of sodium dodecyl sulfate, and ultrasonically disperse it in 100 parts of deionized water, and ensure that the nanosilver particles are evenly dispersed by ultrasonic treatment at a frequency of 50 kHz and a power of 300 W; then mix it with the reduced graphene aqueous dispersion; obtain a composite reaction solution; adjust the solution pH value to 1, stir and react at 0°C for 1 hour, separate the reactant into solid and liquid, and then wash and dry it to obtain reduced graphene-loaded nanosilver, that is, the coated enhanced nanosilver powder.

[0094] Take 12 parts of coated enhanced nano silver powder, add it to 60 parts of deionized water, and disperse it evenly by ultrasonication;

[0095] Take 30 parts of epoxy resin and place them in a high shear mixer for later use;

[0096] Gradually add the coated enhanced nanosilver liquid and 1 part of dispersant sodium dodecyl sulfate into the epoxy resin, stirring while adding;

[0097] Add 6 parts of curing agent diaminocyclohexane and 1.6 parts of plasticizer dibutyl phthalate to the high shear mixer and continue to stir evenly to ensure that the curing agent is completely distributed in the epoxy resin;

[0098] Finally, add 8 parts of ethanol to adjust the coating viscosity;

[0099] The coating was poured into a mold, placed in an oven, and cured at 70° C. for 4 hours to obtain the nano silver coating.

[0100] Comparative Example 1

[0101] According to the weight components, 6 parts of silver nitrate are uniformly dispersed in 100 parts of deionized water to obtain a first reaction liquid; 30 parts of polyethyleneimine are uniformly dispersed in 250 parts of deionized water to obtain a second reaction liquid; the first reaction liquid and the second reaction liquid are mixed, the pH value is adjusted to 1, and the mixture is stirred evenly and fully reacted in an oil bath at 80° C. to obtain a third reaction liquid; the third reaction liquid is filtered, washed and dried to obtain nano silver.

[0102] Take 1 part of nanosilver, add 0.5 parts of chloroacetic acid and dissolve in deionized water, adjust the pH value of the solution to 1, stir and react for 3 hours,

[0103] After the reaction was completed, the mixture was filtered, washed, and cleaned with ethanol three times, and finally dried at 60° C. to obtain chloroacetic acid-modified nanosilver.

[0104] One part of graphite is uniformly dispersed in 50 parts of concentrated sulfuric acid, and 4 parts of concentrated nitric acid are added, stirred in an ice-water bath, and slowly heated to room temperature, and the stirring reaction is continued for 10 hours to generate graphene oxide; after the reaction is completed, it is centrifuged and washed several times to remove residual acidic substances and unreacted impurities, and then dispersed in 200 parts of deionized water to obtain a graphene oxide aqueous dispersion; then ultrasonic treatment is performed with a frequency of 70 kHz, a power of 250 W, and an ultrasonic time of 35 minutes to ensure that the graphene oxide is completely dispersed; then, 5 parts of polyethyleneimine are added to the graphene oxide dispersion, and the stirring reaction is continued for 2.5 hours to obtain a modified graphene oxide dispersion.

[0105] One portion of reducing agent sodium hydride was added to the modified graphene oxide dispersion, and the mixture was stirred for reaction for 2 hours. After the reaction was completed, a reduced graphene aqueous dispersion was obtained.

[0106] Take 1 part of the chloroacetic acid modified nanosilver, add 0.1 part of sodium dodecyl sulfate, ultrasonically disperse in 100 parts of deionized water, and use ultrasonic treatment with a frequency of 50 kHz and a power of 300 W to ensure that the nanosilver particles are evenly dispersed; then mix with the reduced graphene aqueous dispersion; obtain a composite reaction solution; adjust the solution pH value to 1, stir and react at 0°C for 1 hour, separate the reactant into solid and liquid, and then wash and dry to obtain reduced graphene-loaded nanosilver, that is, the coated enhanced nanosilver powder.

[0107] Take 12 parts of coated enhanced nano silver powder, add it to 60 parts of deionized water, and disperse it evenly by ultrasonication;

[0108] Take 30 parts of epoxy resin and place them in a high shear mixer for later use;

[0109] Gradually add the coated enhanced nanosilver liquid and 1 part of dispersant sodium dodecyl sulfate into the epoxy resin, stirring while adding;

[0110] Add 6 parts of curing agent diaminocyclohexane and 1.6 parts of plasticizer dibutyl phthalate to the high shear mixer and continue to stir evenly to ensure that the curing agent is completely distributed in the epoxy resin;

[0111] Finally, add 8 parts of ethanol to adjust the coating viscosity;

[0112] The coating was poured into a mold, placed in an oven, and cured at 70° C. for 4 hours to obtain the nano silver coating.

[0113] Compared with Example 3, Comparative Example 1 omitted the step of coating nanosilver with polyaniline; other operation procedures and process parameters were the same.

[0114] Comparative Example 2

[0115] According to the weight components, 6 parts of silver nitrate are uniformly dispersed in 100 parts of deionized water to obtain a first reaction liquid; 30 parts of polyethyleneimine are uniformly dispersed in 250 parts of deionized water to obtain a second reaction liquid; the first reaction liquid and the second reaction liquid are mixed, the pH value is adjusted to 1, and the mixture is stirred evenly and fully reacted in an oil bath at 80° C. to obtain a third reaction liquid; the third reaction liquid is filtered, washed and dried to obtain nano silver.

[0116] Take 1 part of the nanosilver and 0.1 part of sodium dodecyl sulfate, ultrasonically disperse them in deionized water, then add 3 parts of aniline and 5 parts of ammonium persulfate, adjust the pH value to 1, stir and react at 0°C for 1 hour, then perform solid-liquid separation, wash the obtained solid twice with ethanol and then vacuum dry to obtain polyaniline-coated nanosilver.

[0117] Take 1 part of polyaniline-coated nanosilver, add 0.5 parts of chloroacetic acid and dissolve in deionized water, adjust the pH value of the solution to 1, stir and react for 3 hours,

[0118] After the reaction was completed, the mixture was filtered, washed, and cleaned with ethanol three times, and finally dried at 60° C. to obtain chloroacetic acid-modified polyaniline-coated nanosilver.

[0119] Take 12 parts of chloroacetic acid-modified polyaniline coated nanosilver, add it to 60 parts of deionized water, and disperse it evenly by ultrasonication;

[0120] Take 30 parts of epoxy resin and place them in a high shear mixer for later use;

[0121] Gradually add the coated enhanced nanosilver liquid and 1 part of dispersant sodium dodecyl sulfate into the epoxy resin, stirring while adding;

[0122] Add 6 parts of curing agent diaminocyclohexane and 1.6 parts of plasticizer dibutyl phthalate to the high shear mixer and continue to stir evenly to ensure that the curing agent is completely distributed in the epoxy resin;

[0123] Finally, add 8 parts of ethanol to adjust the coating viscosity;

[0124] The coating was poured into a mold, placed in an oven, and cured at 70° C. for 4 hours to obtain the nano silver coating.

[0125] Compared with Example 3, Comparative Example 2 omitted the step of preparing graphene oxide, and other operation procedures and process parameters were the same.

[0126] Comparative Example 3

[0127] According to the weight components, 6 parts of silver nitrate are uniformly dispersed in 100 parts of deionized water to obtain a first reaction liquid; 30 parts of polyethyleneimine are uniformly dispersed in 250 parts of deionized water to obtain a second reaction liquid; the first reaction liquid and the second reaction liquid are mixed, the pH value is adjusted to 1, and the mixture is stirred evenly and fully reacted in an oil bath at 80° C. to obtain a third reaction liquid; the third reaction liquid is filtered, washed and dried to obtain nano silver.

[0128] Take 1 part of the nanosilver and 0.1 part of sodium dodecyl sulfate, ultrasonically disperse them in deionized water, then add 3 parts of aniline and 5 parts of ammonium persulfate, adjust the pH value to 1, stir and react at 0°C for 1 hour, then perform solid-liquid separation, wash the obtained solid twice with ethanol and then vacuum dry to obtain polyaniline-coated nanosilver.

[0129] One part of graphite is uniformly dispersed in 50 parts of concentrated sulfuric acid, and 4 parts of concentrated nitric acid are added, stirred in an ice-water bath, and slowly heated to room temperature, and the stirring reaction is continued for 10 hours to generate graphene oxide; after the reaction is completed, it is centrifuged and washed several times to remove residual acidic substances and unreacted impurities, and then dispersed in 200 parts of deionized water to obtain a graphene oxide aqueous dispersion; then ultrasonic treatment is performed with a frequency of 70 kHz, a power of 250 W, and an ultrasonic time of 35 minutes to ensure that the graphene oxide is completely dispersed; then, 5 parts of polyethyleneimine are added to the graphene oxide dispersion, and the stirring reaction is continued for 2.5 hours to obtain a modified graphene oxide dispersion.

[0130] One portion of reducing agent sodium hydride was added to the modified graphene oxide dispersion, and the mixture was stirred for reaction for 2 hours. After the reaction was completed, a reduced graphene aqueous dispersion was obtained.

[0131] Take 1 part of the polyaniline-coated nanosilver, add 0.1 part of sodium dodecyl sulfate, and ultrasonically disperse it in 100 parts of deionized water, with the ultrasonic frequency of 50 kHz and the power of 300 W to ensure that the nanosilver particles are evenly dispersed; then mix it with the reduced graphene aqueous dispersion; obtain a composite reaction solution; adjust the solution pH value to 1, stir and react at 0°C for 1 hour, separate the reactant into solid and liquid, and then wash and dry it to obtain the reduced graphene-loaded nanosilver, that is, the coated enhanced nanosilver powder.

[0132] Take 12 parts of coated enhanced nano silver powder, add it to 60 parts of deionized water, and disperse it evenly by ultrasonication;

[0133] Take 30 parts of epoxy resin and place them in a high shear mixer for later use;

[0134] Gradually add the coated enhanced nanosilver liquid and 1 part of dispersant sodium dodecyl sulfate into the epoxy resin, stirring while adding;

[0135] Add 6 parts of curing agent diaminocyclohexane and 1.6 parts of plasticizer dibutyl phthalate to the high shear mixer and continue to stir evenly to ensure that the curing agent is completely distributed in the epoxy resin;

[0136] Finally, add 8 parts of ethanol to adjust the coating viscosity;

[0137] The coating was poured into a mold, placed in an oven, and cured at 70° C. for 4 hours to obtain the nano silver coating.

[0138] Compared with Example 3, Comparative Example 3 omitted the step of modifying polyaniline with chloroacetic acid, and other operation procedures and process parameters were the same.

[0139] The nano silver coatings prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing.

[0140] Antibacterial performance test: refer to the method in HG / T 3950-2007 standard for testing, select the data of Staphylococcus aureus and Escherichia coli after 56 days, and take the average value.

[0141] The wear resistance test is carried out according to GB / T 1768-2006 standard and with the rotating rubber grinding wheel method. Before the test, the sample is prepared first, and the coating is evenly applied to the polished test piece, and the coating thickness is set to 200μm. After coating, the sample needs to be left at room temperature for 10 days before use. When conducting the wear resistance test, the initial mass of the specimen is first weighed, and then the specimen is mounted on the wear meter and connected to the dust collection device. The corresponding load and speed are set, and the speed of this experiment is 100 rpm. The machine automatically stops after starting to the set speed, and the sample is removed and weighed again. By comparing the mass difference of the two weighing results, the weight loss of the sample under specific load and speed conditions is obtained. The smaller the weight loss ratio, the stronger the wear resistance.

[0142] For the antistatic performance test, the initial surface resistance was tested according to the method of SJ / T11294-2003 "General Specification for Antistatic Floor Coatings".

[0143] The test results are shown in Table 1 below.

[0144]

[0145] Antibacterial performance analysis:

[0146] The nano-silver coatings of Examples 1, 2, and 3 showed extremely high antibacterial rates, especially for Staphylococcus aureus, with an antibacterial rate close to 100%. This is because the antibacterial effect of nano-silver mainly depends on the silver ion (Ag + ) are released, and these silver ions can bind to the cell wall and DNA of bacteria, destroy the cell membrane and inhibit bacterial metabolism. The role of polyaniline: polyaniline can promote the release of silver ions through electron transfer in the oxidized state, increase the concentration of silver ions, and further enhance the antibacterial effect. Especially under the synergistic effect of graphene oxide, the release of silver ions is more uniform and lasting, thereby enhancing the antibacterial performance. The synergistic effect of graphene: partially reduced graphene not only provides a conductive channel to promote the rapid release of silver ions, but also may enhance its antibacterial effect through interaction with bacterial cell membranes.

[0147] The antibacterial rate of comparative example 1 is relatively low, especially the antibacterial rate of Staphylococcus aureus is only 93.82%. This is because the silver particles are easily agglomerated without the use of polyaniline-coated nanosilver coating, resulting in a decrease in antibacterial activity. Secondly, the lack of the synergistic effect of polyaniline on the release of silver ions further reduces the antibacterial activity.

[0148] Due to the lack of the synergistic effect of graphene in Comparative Example 2, the overall electron migration speed of the material is reduced, thereby slowing down the release rate of silver ions, resulting in a weakening of its antibacterial ability.

[0149] Wear resistance analysis:

[0150] The coatings of Examples 1, 2, and 3 exhibited lower wear-resistant weight loss rates, indicating that these composite coatings have good wear resistance. This is because the synergistic effect of polyaniline, graphene oxide, and nanosilver improves the mechanical strength and hardness of the coating. In particular, the introduction of graphene enhances the hardness and toughness of the coating, forms a strong network structure, and improves the scratch resistance and wear resistance of the coating.

[0151] Polyaniline coating: The coating of polyaniline effectively prevents the agglomeration of nanosilver and ensures the uniformity of the coating, thereby improving the overall wear resistance of the coating. Graphene mechanical properties: The introduction of graphene enhances the compression and friction resistance of the coating and forms a strong conductive network, which not only improves the conductivity, but also enhances the physical strength of the coating, thereby improving the wear resistance.

[0152] In Comparative Example 1, the nanosilver coating without polyaniline coating showed a higher weight loss rate (8.6%) than Example 3. This difference is due to the lack of the protective effect and coating effect of polyaniline, which leads to a significant decrease in the wear resistance of the coating. Polyaniline coating can enhance the structural stability of the coating, prevent the aggregation or precipitation of silver particles, and enable the coating to better maintain its integrity during friction. The coating without polyaniline lacks this protection, and the coating is easily damaged by friction, resulting in a higher weight loss rate.

[0153] The weight loss rate of comparative example 2 reached 12.1%. This difference shows that the coating without composite graphene lacks the necessary strength and stability, resulting in easy wear of the coating.

[0154] In the case of no chloroacetic acid-modified polyaniline in Comparative Example 3, the binding force between polyaniline and epoxy resin and other components is weak. Without the help of carboxylic acid groups, the adhesion between polyaniline and the substrate is poor, resulting in the coating being easily detached during friction and wear, resulting in a high wear weight loss.

[0155] Antistatic performance analysis:

[0156] Resistance is an important indicator of conductive materials. Generally, the smaller the resistance, the better the conductivity of the material, and the stronger the corresponding antistatic property. Antistatic property refers to the ability of a material to quickly release charge when encountering charge accumulation, thereby avoiding static electricity accumulation and reducing static electricity discharge. For coatings, good antistatic property means that the surface resistance of the coating is low.

[0157] From the data in Table 1, it can be seen that the surface resistance of Examples 1, 2, and 3 is significantly lower than that of Comparative Groups 1, 2, and 3, indicating that the coatings of the Examples have better electrical conductivity and antistatic properties.

[0158] In Comparative Example 1, there is no polyaniline to coat the nanosilver particles, resulting in agglomeration of the silver particles in the coating, reducing the effective surface area of ​​the silver and thus reducing the electron conduction efficiency. In addition, the lack of the electron transfer effect of polyaniline results in an unsmooth conduction path and a high resistance.

[0159] The lack of graphene in Comparative Example 2 results in the coating lacking an effective conductive network. Graphene not only provides a channel for electron transfer for polyaniline, but also helps improve the dispersibility of nanosilver. In the absence of graphene, the migration efficiency of electrons is low, resulting in poor conductivity and high surface resistance of the coating.

[0160] In Comparative Example 3, the lack of chloroacetic acid-modified polyaniline results in insufficient polarity of polyaniline, resulting in poor compatibility with epoxy resin and graphene, affecting the formation of a conductive network. The oxidation state of polyaniline cannot fully promote the release of silver ions, reducing the conductivity of the coating, resulting in a high surface resistance, which is not conducive to the elimination of static electricity.

[0161] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing coated enhanced nano silver powder, characterized in that: The steps include: S1: Silver nitrate was used as the silver source and polyethyleneimine was used as the reducing agent to prepare nanosilver; S2: using aniline and ammonium persulfate to coat and modify the nano-silver under acidic conditions to obtain polyaniline-coated nano-silver; S3: using chloroacetic acid to modify the polyaniline-coated nanosilver to obtain chloroacetic acid-modified polyaniline-coated nanosilver; S4: oxidizing graphite to prepare graphene oxide, and then modifying it with polyethyleneimine to obtain a modified graphene oxide dispersion; S5: partially reducing the graphene oxide using sodium hydride to obtain a reduced graphene aqueous dispersion; S6: using reduced graphene oxide to load the chloroacetic acid modified polyaniline to coat the nano-silver, to obtain the coated enhanced nano-silver powder.

2. A method for preparing the coated enhanced nano silver powder according to claim 1, characterized in that: The specific process of step S1 is: According to the weight components, 5-8 parts of silver nitrate are uniformly dispersed in 100 parts of deionized water to obtain a first reaction liquid; 25-40 parts of polyethyleneimine are uniformly dispersed in 250 parts of deionized water to obtain a second reaction liquid; the first reaction liquid and the second reaction liquid are mixed, the pH value is adjusted to 1-2, and the mixture is stirred uniformly and fully reacted in an oil bath at 80-100° C. to obtain a third reaction liquid; the third reaction liquid is filtered, washed and dried to obtain nano silver.

3. A method for preparing the coated enhanced nano silver powder according to claim 1, characterized in that: The specific process of step S2 is: take 1 part of the nanosilver and 0.1-0.2 parts of sodium dodecyl sulfate, ultrasonically disperse them in deionized water, then add 1.7-3.4 parts of aniline and 4-6 parts of ammonium persulfate, adjust the pH value to 1-2, stir the reaction at 0-5°C for 1-2h, then perform solid-liquid separation, wash the obtained solid with ethanol and then dry it to obtain polyaniline-coated nanosilver.

4. A method for preparing the coated enhanced nano silver powder according to claim 1, characterized in that: The specific process of step S3 is: Take 1 part of polyaniline-coated nanosilver, add 0.5-1.5 parts of chloroacetic acid and dissolve in deionized water, adjust the pH value of the solution to 1-2, stir and react for 3-5 hours, After the reaction is completed, the mixture is filtered, washed, and cleaned with ethanol, and finally dried at 60-80° C. to obtain chloroacetic acid-modified polyaniline-coated nanosilver.

5. A method for preparing coated enhanced nano silver powder according to claim 1, characterized in that: The specific process of step S4 is as follows: 1-2 parts of graphite are uniformly dispersed in 50 parts of concentrated sulfuric acid, and 4-10 parts of concentrated nitric acid are added, stirred in an ice water bath, and slowly heated to room temperature, and stirred for 6-12 hours to generate graphene oxide; after the reaction is completed, centrifugal washing is performed multiple times to remove residual acidic substances and unreacted impurities, and dispersed in 200 parts of deionized water to obtain a graphene oxide aqueous dispersion; then ultrasonic treatment is performed at a frequency of 40-80 kHz, a power of 200-300W, and an ultrasonic time of 30-40min to ensure that the graphene oxide is completely dispersed; then, 2-8 parts of polyethyleneimine are added to the graphene oxide dispersion, and the stirring reaction is continued for 2-3h to obtain a modified graphene oxide dispersion.

6. A method for preparing coated enhanced nano silver powder according to claim 1, characterized in that: The specific process of step S5 is: adding 1-2 parts of reducing agent sodium hydride to the modified graphene oxide dispersion, stirring and reacting for 2-3 hours to obtain a reduced graphene aqueous dispersion.

7. A method for preparing coated enhanced nano silver powder according to claim 1, characterized in that: The specific process of step S6 is: take 1 part of the chloroacetic acid modified polyaniline coated nanosilver, add 0.1-0.2 parts of sodium dodecyl sulfate, ultrasonically disperse it in 100 parts of deionized water, and perform ultrasonic treatment at a frequency of 40-60 kHz and a power of 200-400 W to ensure that the nanosilver particles are evenly dispersed; then mix it with the reduced graphene aqueous dispersion; obtain a composite reaction solution; adjust the solution pH value to 1-1.5, stir the reaction at 0-5°C for 1-2h, separate the reactant into solid and liquid, and then wash and dry it to obtain reduced graphene-loaded nanosilver, that is, the coated enhanced nanosilver powder.

8. Use of the coated enhanced nano silver powder prepared by the preparation method according to any one of claims 1 to 7 in coatings.

9. A nano silver coating, characterized in that: include: 10-15 parts of coated enhanced nano silver powder, 30-40 parts of epoxy resin, 5-10 parts of curing agent diaminocyclohexane, 1-2 parts of dispersant sodium dodecyl sulfate, 0.5-2 parts of plasticizer dibutyl phthalate and 5-10 parts of ethanol; the coated enhanced nano silver powder is prepared by the method described in any one of claims 1-7.

10. A method for preparing the nano silver coating according to claim 9, characterized in that: The steps include: Take 10-15 parts of coated enhanced nano silver powder, add it to 60 parts of deionized water, and disperse it evenly by ultrasonication; Take 30-40 parts of epoxy resin and place them in a high shear mixer for later use; Gradually add the coated enhanced nanosilver liquid into the epoxy resin while stirring; Add 5-10 parts of curing agent diaminocyclohexane and 0.5-2 parts of plasticizer dibutyl phthalate to the high shear mixer and continue to stir evenly to ensure that the curing agent is completely distributed in the epoxy resin; Finally, add 5-10 parts of ethanol to adjust the viscosity of the coating; The coating is poured into a mold, placed in an oven, and cured at 60-80° C. for 2-4 hours to obtain the nano silver coating.

Citation Information

Patent Citations

  • Magnetic graphene oxide nano-silver composite material and preparation and application thereof

    CN104707991A

  • Preparing method of ionic liquid functionalized graphene / conductive polyaniline nanowire composition material

    CN105601914A

  • Preparation method of water-dispersible conducting graphene

    CN106744834A

  • Modified polyethyleneimine / nano silver composite material and preparation method thereof

    CN109438699A

  • Nano-silver / graphene / cellulose fiber composite material with polyethyleneimine as binder and preparation method of nano-silver / graphene / cellulosic fiber composite material

    CN109440475A

Cited By

  • Preparation process of graphene reinforced porous hollow polyester fiber

    CN121228393A

  • Coating enhanced nano silver powder and preparation method thereof

    CN121514517A